Comparative Evaluation of Productivity and Water Supply in Lower Büyük Menderes and Lower Gediz Basin Water User Associations - Selin AKÇAY; Safiye Pınar TUNALI (Türkiye Tarımsal Araştırmalar Dergisi, 2016)
Comparative analysis of irrigation performance across irrigation systems allows determining how well a system is performing in relation to others. In this research, Akçay Right and Left Bank, Aydın and Söke Water User Associations located in Lower Büyük Menderes Basin and Menemen Right and Left Bank Water User Associations located in Lower Gediz Basin were assessed by using benchmarking applications in irrigation and drainage. As a result of the study, output per cropped area, output per unit command, output per unit irrigation supply, output per unit water consumed, relative water supply, relative irrigation supply and annual irrigation water delivery per unit irrigated area were determined as 2048-3414 $ ha-1, 1707-2824 $ ha-1,0.30-0.60 $ m-3, 0.27-0.46 $ m-3,1.02-1.60, 0.62-0.95 and 5965-11043 m3 ha-1 respectively. The main problems determined by this study are the improper use of water and inadequate water allocation especially to the downstream water user associations. Agricultural production values of the water user associations are relatively higher than those having similarities and similar functions.